2014
DOI: 10.18637/jss.v060.i03
|View full text |Cite
|
Sign up to set email alerts
|

Spectral Projected Gradient Methods: Review and Perspectives

Abstract: Over the last two decades, it has been observed that using the gradient vector as a search direction in large-scale optimization may lead to efficient algorithms. The effectiveness relies on choosing the step lengths according to novel ideas that are related to the spectrum of the underlying local Hessian rather than related to the standard decrease in the objective function. A review of these so-called spectral projected gradient methods for convex constrained optimization is presented. To illustrate the perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
123
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(126 citation statements)
references
References 106 publications
1
123
0
2
Order By: Relevance
“…They introduce a new globalization approach combining nonmonotone watchdog technique with line search rules. A detail survey on Barzilai-Borwein method-review and perspectives can be found in [19].…”
Section: An Iterative Methods For Solving the Discrete Problemmentioning
confidence: 99%
“…They introduce a new globalization approach combining nonmonotone watchdog technique with line search rules. A detail survey on Barzilai-Borwein method-review and perspectives can be found in [19].…”
Section: An Iterative Methods For Solving the Discrete Problemmentioning
confidence: 99%
“…Due to its simplicity and numerical efficiency, the spectral gradient as well as the spectral projected gradient method has been applied successfully to finding local minimizers of large scale problems [3,4,7,11,14,15,19,27], for more details, see the recent paper [5] and references therein.…”
Section: Then the Secant Equation Becomesmentioning
confidence: 99%
“…Recently, the BB method and its variants have been successfully extended to general unconstrained problems [35], to constrained optimization problems [3,28] and to various applications [29,30,32]. One may see [4,10,17,21,37] and the references therein. Let {ξ 1 , ξ 2 , .…”
Section: Introductionmentioning
confidence: 99%